2016
DOI: 10.1111/jnc.13900
|View full text |Cite
|
Sign up to set email alerts
|

The regulator of calcineurin 1 increases adenine nucleotide translocator 1 and leads to mitochondrial dysfunctions

Abstract: The over-expression of regulator of calcineurin 1 isoform 1 (RCAN1.1) has been implicated in mitochondrial dysfunctions of Alzheimer's disease; however, the mechanism linking RCAN1.1 over-expression and the mitochondrial dysfunctions remains unknown. In this study, we use human neuroblastoma SH-SY5Y cells stably expressing RCAN1.1S and rat primary neurons infected with RCAN1.1S expression lentivirus to study the association of RCAN1 with mitochondrial functions. Our study here showed that the over-expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Alternative explanations for the decline in coupling efficiency are activation of protective compensatory mechanisms or a direct impact of RCAN1 on mitochondrial coupling. Along these lines it is relevant to note that RCAN has been reported to interact both directly 45 and indirectly 46 with the adenine nucleotide translocase, a protein which can act to uncouple the inner mitochondrial membrane proton gradient. 47…”
Section: Discussionmentioning
confidence: 99%
“…Alternative explanations for the decline in coupling efficiency are activation of protective compensatory mechanisms or a direct impact of RCAN1 on mitochondrial coupling. Along these lines it is relevant to note that RCAN has been reported to interact both directly 45 and indirectly 46 with the adenine nucleotide translocase, a protein which can act to uncouple the inner mitochondrial membrane proton gradient. 47…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous studies, RCAN1.1 has been proved to be upregulated in the brain of Down syndrome and Alzheimer's disease, inducing neuronal apoptosis 16 . Recently, we reported that RCAN1.1 is a novel RNA‐binding protein, increasing the adenine nucleotide translocator 1 mRNA, to regulate mitochondrial dysfunctions and neuronal apoptosis 26,38 . However, the distribution and function of RCAN1.4 in the brain have not been characterized in detail, and the effect of RCAN1.4 on ischemic stroke pathogenesis has not been clearly clarified.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recently, we reported that RCAN1.1 is a novel RNAbinding protein, increasing the adenine nucleotide translocator 1 mRNA, to regulate mitochondrial dysfunctions and neuronal apoptosis. 26,38 However, the distribution and function of RCAN1.4 in the brain have not been characterized in detail, and the effect of RCAN1.4 on ischemic stroke pathogenesis has not been clearly clarified. In the present study, we demonstrated that was significantly upregulated in the infarct region of the MCAO model of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in lung ischemia-reperfusion (I/R) injury, the protective administration of cyclosporine-A would depend on the decreased expression levels of ANT1 and VDAC1 [ 118 ]. Furthermore, ANT1 overexpression was deleterious in various cell types [ 86 , 87 , 119 ]. ANT1 up-regulation via the overexpression of regulator of calcineurin 1 isoform 1 was detrimental in human neuroblastoma SH‐SY5Y cells, leading to abnormal mitochondria [ 119 ].…”
Section: Discussionmentioning
confidence: 99%